Organisational Learning at Team Level and Perceived Employability: an Empirical Examination - Wiśniewska, Sylwia; Wiśniewski, Kamil; Szydło, Robert (Organizacyjne uczenie się na poziomie zespołu a postrzegana zatrudnialność: badanie empiryczne, 2025)
Aim: The article aimed to explore the relationship between organisational learning solutions at team level and perceived employability in the modern labour market, according to the opinions of the team members surveyed. Methodology: The author reviewed the existing literature on perceived employability and organisational learning, and analysed the empirical research results using various tools, including general descriptive statistics, statistical tests, and the Covariance-Based Structural Equation Modelling (CB-SEM) method. Results: The analysis revealed the three subgroups of solutions at the team level of organisational learning, namely internal solutions, experience-based solutions, and external solutions. With the flow of CB-SEM analysis, it appeared that only the experience-based solutions were affecting the perceived impact on employability. Based on the research results, it can be concluded that teamwork is an excellent platform for the formal and informal exchange of opinions, contributing to the development of the perceived employability of team members. Implications and recommendations: The proposed implications relate to a work environment that allows for a casual exchange of views and a formal exchange of opinions. The formal and informal exchanges of opinions provide opportunities to confront views on professional issues with those who view them from their perspective, for example enable the dissemination of good practices within a team. Originality/value: For the first time, the author empirically investigated the relationships between organisational learning at team level and the employability of team members. The contribution of this study was to bring a work environment perspective to shaping the internal employability of team members. The literature studies confirmed the lack of research in this field.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2025; vol. 69, nr 2, s. 164-179